Penerapan Model Pembelajaran Group Investigation untuk Meningkatkan Hasil Belajar Peserta Didik pada Tema Panas dan Perpindahannya Muatan IPA Kelas V SD Negeri 215/X Sungai Toman Semester Genap Tahun Ajaran 2021/2022 - Rumiati Rumiati (Departement of Mathematics Education, 2022)
This study aims to obtain information and discuss the application of the group investigation learning model to improve student learning outcomes on the theme of heat and transfer of science content for class V SD Negeri 215/X Sungai Toman even semester of the 2021/2022 academic year. This research is a classroom action research which consists of two cycles. This research was conducted at 215/X Sungai Toman for the 2021/2022 academic year, even semester, with 24 class V students as research subjects. Data collection techniques using tests, observations, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it can be concluded that through the application of the group investigation learning model it can improve student learning outcomes on the theme of heat and the transfer of science content in class V SD Negeri 215/X Sungai Toman even semester of the 2021/2022 school year which is marked by an increase in learning outcomes and student completeness from cycle I to cycle II and with the act of giving rewards